Pattern of oral and dental diseases among children attending Dental dept. in Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh: A cross sectional hospital based study (Update Dental College Journal, 2020)
Introduction: Oral and dental health isthe standard of the oral and related tissue, which enables an individual to eat, speak, and socialize without active discomfort and embarrassment and which contributes to general well-being of the individualObjective: To find out Pattern of oral and dental diseases among children attending Dental Department in Dhaka Shishu (Children) Hospital, Dhaka, BangladeshMaterials and Methods:This was a cross sectional hospital based study carryout among 443 childrens (242 males and 201 females) attending in the Department of Paediatric dentistry in Dhaka Shishu (Children) Hospital.All the new patients attending to Dental OPD with the complained of oral and dental problems were included in this study. Old patients and those who were not willing to participate in the clinical examination for study were excluded from the study. The study period was October 2018 to December 2018Results: The study was carried out among (443) children were 242 (54.6%) males and 201 (45.4%) females a male-female ratio of 1.2:1.The age range of children were 224 (50.6%) below the, age of 5 years, 200 (45.1%) at the age of 5-10 years and 19(4.3%) above 10 years (10- 14 years).Out of 443 children 157 (22.7%) showed presence of dental caries, 138 (19.9%) had grossly destructed carious teeth, 79 (11.5%) had dentolveolar abscess, 53 (7.7%) had retained broken root, 52(7.6%) were suffering from pulpitis, 108 (15.7%) of the children presented with stomatitis, 34 (4.8%) had retained decidous teeth,24(3.5%) geographical tongue , 24(3.5%) oral thrush, 7(1.0%) gingivitis 7(1.0%) presented with traumatic injury of tooth, soft tissue and bony tissue, 4(0.5%) had pericoronitis, 1(0.1%) had natal tooth and 4(0.5%) were others like extra oral swelling, apthus ulcer , mucoceale. The total Association of dental disease with different age 10 yrs. 4.4%. Among them Caries disease all group average high rate so p-Value (0.010*). So grossly destructed due to caries 49 cases of 5 yrs. 35.5%, 85 cases of 5-10yrs. 54.1%, and 7 cases of under 15yrs. 5.1% significant.Conclusion: Dental caries was the most predominant disease in the children followed by dentoalveolar abscess. Oral health promotion and planning programs directed towards the oral health should be conducted at regular intervals.Update Dent. Coll. j: 2020; 10 (2): 6-9